Bersama Mencegah Bullying, Menjadi Teman yang Baik dan Peduli - Ahmadi Hasan; Nina Sri Savarina Ulfah; Nida Fitriani; Anik Priamita Lutfhiana; Norliana; Muhammad Azka Munawwir (PT. Sharia Journal and Education Center, 2024)
Bullying prevention in the school environment is a big challenge for various parties, especially educators and parents. Bullying not only adversely affects the mental health of the victim, but can also create an unsafe and unconducive school environment (Siti and Siful, 2022). Through socialization activities with the theme “Together Preventing Bullying: being a Good and Caring Friend”, this program aims to empower students of SDN Kebun Bunga 6 to be more aware of the importance of empathy and caring for others. The method used in this program is offline sharing, which involves direct communication between the speaker and the participants. This activity is expected to increase students' understanding of bullying and form a more positive mindset and behavior in social interactions at school. The implementation of the activity took place for one hour on September 26, 2024, with evaluation conducted to assess the effectiveness of this activity.